Peran Komunikasi Dalam Penyuluhan di Desa Aekraja - Sriayu Sibarani; Raikhapoor Raikhapoor (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to analyze the role of communication media in the extension process in Aekraja Village. Communication media, especially interpersonal communication, is considered to have a significant influence in conveying information and building relationships between extension workers and the Aekraja village community. This research uses a qualitative approach with in-depth interviews and observation methods. The results of the research show that interpersonal communication, such as face-to-face dialogue and group discussions, is the main effective medium in the counseling process in Aekraja Village. This is due to its ability to convey messages directly, provide feedback opportunities, and create trust between extension agents and the community. However, this research also found several challenges, such as low levels of media literacy and differences in understanding between individuals, which affect the success of extension. T